2016
DOI: 10.1037/pro0000111
|View full text |Cite
|
Sign up to set email alerts
|

What you should want from your professional: The impact of educational information on people’s attitudes toward simple actuarial tools.

Abstract: in Ontario, Canada. His primary research program involves improving law enforcement procedures through psychological science, with a particular focus on investigative interviewing. He is also interested in people's perception of decision making strategies used by practitioners both inside and outside the justice system. KIRK LUTHER received his MSc and PhD in experimental psychology from Memorial University. His research pertains primarily to the study of human behavior within the criminal justice system, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…decision-makers' actual decision-rule use, instead of only use intentions (e.g., Eastwood & Luther, 2016) or self-reported use. Furthermore, this allowed us to investigate the effect of educational information on prediction accuracy.…”
Section: Improving Decision Makingmentioning
confidence: 99%
See 3 more Smart Citations
“…decision-makers' actual decision-rule use, instead of only use intentions (e.g., Eastwood & Luther, 2016) or self-reported use. Furthermore, this allowed us to investigate the effect of educational information on prediction accuracy.…”
Section: Improving Decision Makingmentioning
confidence: 99%
“…Another, more fundamental, reason is that many decision makers lack relevant knowledge of evidence-based decision-making practices (Fisher et al, 2020; Jackson et al, 2018; Lawler, 2007; Rynes, 2012; Rynes et al, 2002; Sanders et al, 2008). For example, decision makers believe that they can learn from their prediction errors, can accurately identify incorrect decision-rule predictions that warrant deviation from a rule, and can make more accurate holistic judgments with experience (Dietvorst et al, 2015; Eastwood & Luther, 2016; Highhouse, 2008; Leonard & Swap, 2004). However, in noisy contexts such as human performance prediction, these beliefs are incorrect (Dawes, 1971; Goldberg, 1968; Grove et al, 2000; Jackson et al, 2019; Karelaia & Hogarth, 2008; Yu & Kuncel, 2020).…”
Section: Improving Decision Makingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Kaplan et al (2001) showed in an accountancy bond rating task that decision makers were more likely to use a mechanical rule when they could design the rule. Furthermore, informing decision makers in a legal judgment scenario that mechanical rule predictions are more accurate than holistic predictions increased their intention to support the use a mechanical rule in practice (Eastwood & Luther, 2016).…”
Section: Evaluation Of the Selection Proceduresmentioning
confidence: 99%